SELEKSI LANJUT KULTIVAR PADI SAWAH LOKAL KALIMANTAN TIMUR - Rusdiansyah, Tjatjuk Subiono, dan Muhammad Saleh (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The purpose of selection were to get a local lowland rice cultivar shave superior agronomic traits and high yield and get purified seed stock as the base material of plant propagation.Selection was conducted in Karang Tunggal village of Tenggarong Seberang sub district of Kutai Kartanegara Regency from April to August 2014.  Selection was arranged in a randomized complete block design (RCBD) with four replications.  Further selected cultivars that v1 = Kambang; v2 = Roti; v3 = Sikin Putih; v4 = Sikin Merah; v5 = Popot; v6 = Pudak; and v7 = Situbagendit (check cultivar).  Data were analyzed with variance at 5% level and if there was significant followed by Least Significant Difference test (LSD) at 5% level.The results showed that there were three cultivars namely Roti, Sikin Putih and Sikin Merah have agronomic traits and yield meet the selection criteria.  Cultivars Kambang meet the selection criteria despite having a total number of grains and grain content of less, but has a short stem, the total number of tillers and productive tillers per hill at most, the percentage of filled grain/panicle >80% and the production of grain/ha > 5.0 t.  Pudak cultivar has agronomic traits and yield appropriate selection criteria, but it has a long harvesting.  Selection results have been obtained seed stocks were purified as plant propagation material.